Factors Identification in Micro and Small Business Production Employee Turnover in at West Bandung - Rochman, Didit Damur; Rahmana, Arief (CENTRAL ASIA AND THE CAUCASUS, 2022)
Micro, small and medium enterprises (MSME) were the pillars of the Indonesian economy during the 2008-2009 economic crisis. One of the problems that causes low productivity is employee turnover. This paper identifies the causes of employee turnover using the AHP method on the factors causing employee turnover including job satisfaction, organizational commitment, job insecurity, perceived alternative opportunity. The results obtained are job satisfaction and perceived alternative opportunity are factors that have weights of 0.545 and 0.289. The sub-factors of job satisfaction, promotion opportunities and co-workers have weights of 0.53 and 0.3. Then the perceived alternative opportunity sub-factor for better financial and career offers in other MSMEs has a weight of 10%.